TEACHERS QUESTIONING STRATEGIES IN ELT - Rizka Indahyanti; Muthmainnah Mursidin; Nadya Nadya (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2023)
This research examines the questioning strategy used by teachers during classroom interactions in English Language Teaching (ELT). Attending classes in grades X and XII. A study was done to investigate the types of questions used by English teachers in English language instruction (ELT) and the role of teachers' questioning methods in ELT classrooms. The study was carried out at UPT SMA Negeri 7 Enrekang. This study use qualitative descriptive methodology. The instruments utilized for data collection include interviews, observation, and documentation. Two English professors participated as responses. The research findings indicate that English teachers at UPT SMA Negeri 7 Enrekang utilize several sorts of questions with specific functions during the learning process. 1. Display questioning; 2. Procedural Questions; 3. Referential Questions. The subsequent function inquiries are as follows: 1. Diagnostic function; 2. Instructional role; 3. Motivational function. These findings can serve as a guide for teachers to improve the way they pose questions in language classes, particularly by considering students' past knowledge on the issue to elicit better responses. The diagnostic, instructional, and motivational functions are crucial for teachers to effectively control their communication during the teaching and learning process. Through these functions, teachers can engage students in lessons, stimulate their thinking, and present them with challenging problems to contemplate.